THE ANOMALOUS MAGNETIC FIELD AND ITS DYNAMICS USED TO STUDY THE DEEP STRUCTURE AND MODERN GEODYNAMIC PROCESSES OF THE URALS - Shapiro V.A.; Fedorova N.V.; Nikonova F.I.; Dyakonova A.G.; Tsirulsky A.V.; Chursin A.V.; Turmina L.O. (My University, 1986)
A special aeromagnetic survey was carried out along six east-west geotraverses crossing the Urals at 52°, 54°, 56°, 58°, 60°, 62° N. The long-wavelength component of the anomalous magnetic field (AMF), containing information about the distribution of the magnetization with depth, was separated out. The main crustal structures of the Urals are characterized by a relatively low total magnetization. The large magnetic rock massifs extending to the bottom of the magnetoactive layer are delineated. Since 1969, the dynamics of the AMF have been studied for the territory covering the Urals from 51° N to 58° N. Two extensive meridional anomalous zones Bashkiria and Butka, 40–60 km in width, were delineated. These zones separate the main Urals structures from the neighbouring regions of the East-European platform and West-Siberian plate. Even at the present time, active tectonic processes are occurring in these zones which are reflected in the physical fields. Electrometrical investigations showed an anomalously high conductivity. Geodetic methods revealed that the Bashkiria and Butka anomalies were characterized by noticeable recent vertical movements and deformations of the Earth's crust. The joint analysis of the magnetic and electric-fields data allows of deducing new and important information about the deep structure and tectonic zoning of the Urals, of delineating structures active at the present, and of providing information about the nature of modern geodynamic processes.